2010
DOI: 10.1177/1078390310362264
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Race on Mental Health Service Utilization Among African Americans and Whites With Severe Mental Illness

Abstract: It is possible that the geographic location of the study, equal access to services, and equal rates of substance use between racial groups explain the lack of racial differences found in this sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Likewise, language barriers may also hinder minorities from receiving the mental health services they need (Alegría et al, 2002). However, other studies did not find a significant correlation between race/ethnicity and the utilization of mental health services (Banta, James, Haviland, & Andersen, 2013; Decoux Hampton, Chafetz, & White, 2010).…”
mentioning
confidence: 76%
“…Likewise, language barriers may also hinder minorities from receiving the mental health services they need (Alegría et al, 2002). However, other studies did not find a significant correlation between race/ethnicity and the utilization of mental health services (Banta, James, Haviland, & Andersen, 2013; Decoux Hampton, Chafetz, & White, 2010).…”
mentioning
confidence: 76%
“…However, findings are relatively inconsistent as several other studies have identified no such biases among patients of different ethnicities [5-7]. Research in this area is extensive and the bulk of studies have focused on patients with schizophrenia [8-11].…”
Section: Introductionmentioning
confidence: 99%